PROSPECTS FOR SEARCHING MULTITARGET TOPOISOMERASE INHIBITORS WITH ANTITUMOR PROPERTIES - M. I. Treshchalin; E. V. Neborak; H. M. Treshalina (Сибирский онкологический журнал, 2019)
Purpose of research: to identify the prospects of search for new antitumor non-camptothecin inhibitors of topoisomerase I/II among the various chemical compounds based on the analysis of side effects.Material and Methods. The analysis included 65 relevant literature sources for 2002–2018 years, found in Systems such as Scopus, Web of Science, Pubmed, and eLIBRARY.Results. The antitumor and side effect characteristics of the agents, associated with the selective suppression of the activity of type I and/or II topoisomerase (Top1, Top2) in tumor cells were emphasized. Examples of the relationship between side effects of inhibitors and their structure and catalytic mechanisms were given. The following factors were highlighted as significant: 1) blocking of cells in G2 and S phases with a delay of entry into mitosis; 2) inhibition of the reaction of re-ligation with DNA breaks without re-linking; 3) launching of cytotoxic events with the inhibition of DNA replication and generation of double-strand breaks. Incurable cancers, such as gastric cancer, colorectal cancer, non-small cell lung cancer, hepatocellular carcinoma, glioblastoma, etc. were determined as more sensitive to inhibitors. Side effects of treatment and their connection with the mechanism of activity were described.Conclusion. Based on the comparative analysis of prognostically valuable data regarding the efficacy and safety of topoisomerase I/II inhibitors, multitargeted heterocyclic condensed nitrogen-containing compounds, in particular, anthrafurans, can be considered as new promising clinical candidates with higher selectivity of action.